Chemical composition and phytochemical properties of mango (mangifera indica.)seed kernel - Orijajogun, Joyce; Batari, Latayo; aguzue, onyinye; Aguzue, Onyinye (International Journal of Advanced Chemistry, 2014)
The seed kernel of (Mangifera indica) obtained from Kwali FCT,Abuja were studied for the phytochemical,proximate analysis and mineral composition. The proximate composition reveals; moisture (5.9%), Ash (2.43%), crude protein (5.20%), carbohydrate (76.14%) and crude fibre (0.49%).The result of the mineral composition showed potassium (116.9ppm), sodium (23.1ppm), calcium (0.26ppm) and magnesium (0.56ppm). The result of phytochemical studies of extract show the presence of alkaloids, steroids, tannins, phenol, resins, glycoside and volatile oil but saponins and phlobatannins are absent. The presence of some of these metabolites confirms the usefulness of the plant in the treatment of various diseases. Keywords: Mangifera Indica, Phytochemical, Proximate Composition and Metabolites.